2004
DOI: 10.1093/jac/dkh424
|View full text |Cite
|
Sign up to set email alerts
|

Community and hospital spread of Escherichia coli producing CTX-M extended-spectrum β-lactamases in the UK

Abstract: CTX-M-producing E. coli are a rapidly developing problem in the UK, with CTX-M-15 particularly common. The diversity of producers and geographical scatter of referring laboratories indicates wide dissemination of blaCTX-M genes. Because of the public health implications, including for the treatment of community-acquired urinary tract infections, the spread of these strains--and CTX-M-15 beta-lactamase in particular--merits close monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
293
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(334 citation statements)
references
References 24 publications
37
293
2
2
Order By: Relevance
“…CTX-M enzymes have been found predominantly in members of the Enterobacteriaceae, most prevalently in E. coli, K. pneumoniae and Salmonella enterica serovar Typhimurium in South America (Radice et al, 2002;Villegas et al, 2004) and Europe (Baraniak et al, 2002;Batchelor et al, 2005;Livermore & Hawkey, 2005), although they are rarely isolated in Japan (Yagi et al, 2000). The spread of CTX-M enzyme-producing E. coli among community-and hospital-based patients has also been reported (Woodford et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…CTX-M enzymes have been found predominantly in members of the Enterobacteriaceae, most prevalently in E. coli, K. pneumoniae and Salmonella enterica serovar Typhimurium in South America (Radice et al, 2002;Villegas et al, 2004) and Europe (Baraniak et al, 2002;Batchelor et al, 2005;Livermore & Hawkey, 2005), although they are rarely isolated in Japan (Yagi et al, 2000). The spread of CTX-M enzyme-producing E. coli among community-and hospital-based patients has also been reported (Woodford et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These isolates, which were from six different hospitals and a variety of clinical sources (urine, blood, faeces, sputa and wounds), all produced CTX-M-15 and were believed to comprise a single epidemic strain, designated strain A. Four other major PFGE clusters of related E. coli isolates producing CTX-M-15 were also noted and were designated B to E. Representative isolates of each of the five clusters belonged to the same serotype (O25) and given their close relationship by PFGE (78% similarity), the study investigators suggested they may have had a common ancestry [60]. Subsequent analysis using MLST showed that strains A-E all belonged to an extremely successful clone of E. coli of ST131 which is now known to have disseminated globally [62,63].…”
Section: (I) Enhanced Surveillance Of Methicillin-resistant Staphylocmentioning
confidence: 91%
“…Current UK surveillance data have shown that the majority of bloodstream isolates of E. coli and K. pneumoniae remain susceptible to meropenem, with resistance being seen in 0.1% and 0.9%, respectively in 2013 [49,50]. However, there are clear signs that resistance is nonetheless emerging, with the number of isolates of Gram-negative bacteria noted from about 2000 onwards, with cephalosporin resistance increasingly being seen in E. coli producing CTX-M type ESBLs, particularly CTX-M-15 [59][60][61]. In addition, while ESBL-mediated cephalosporin resistance seen during the 1990s had primarily occurred in hospitals, many of the CTX-M-producing isolates of E. coli were initially obtained from patients in the community [60].…”
Section: (I) Enhanced Surveillance Of Methicillin-resistant Staphylocmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of bla TEM , bla SHV, bla CTX-M genes and bla PER-1 genes was determined for E. coli strains by polymerase chain reaction (PCR) using primers and conditions as described previously [25][26][27][28]. In brief, bacterial DNA was extracted by boiling and applied to PCRamplification using Taq polymerase (Invitrogen, Germany) under the following conditions: 94°C for 5 min, 35 cycles consisting of 95°C for 30s, 55°C for 30s, and 72°C for 50s each, followed by a final extension at 72°C for 8 min.…”
Section: Characterization Of Extended-spectrum β-Lactamasesmentioning
confidence: 99%